2018
DOI: 10.18203/2320-6012.ijrms20183626
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the relationship between personal characteristics with lip, jaw and philtrum dimensions

Abstract: Background: The relationship between the sizes of the structures that form our face, such as lips, philtrum, and the jaw, and our personality characteristics are unknown. In this study, it was scientifically researched whether lip, jaw and philtrum anatomy can give us clues on personality characteristics or not.Methods: The photographs of the university students were taken using digital camera in two positions. The students who were photographed were asked to simultaneously complete personality test. The photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
4
0
1
Order By: Relevance
“…In a study conducted on 76 females and 76 males individuals between the ages of 17 and 25, Kosif [27] found lower facial height as 77.54 ± 8.16 mm in women and as 86.70 ± 9.87 mm in men; total nasal length as 52.34 ± 8.05 mm in women and as 56.49 ± 5.86 mm in men; nose width as 41.65 ± 2.24 in women and as 44.62 ± 4.59 mm in men. In this study, we found lower facial height media value as 5.95 cm in the first group, as 6.20 cm in the second group, as 6.17 cm in the third group and as 6.20 cm in the fourth group; total nasal length median value as 5.25 cm in the first group, as 5.69 cm in the second group, as 5.88 cm in the third group and as 5.25 cm in the fourth group; nose width median value as 3.41 cm in the first group, as 3.47 cm in the second group, as 3.65 cm in third group and as 3.37 cm in the fourth group.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted on 76 females and 76 males individuals between the ages of 17 and 25, Kosif [27] found lower facial height as 77.54 ± 8.16 mm in women and as 86.70 ± 9.87 mm in men; total nasal length as 52.34 ± 8.05 mm in women and as 56.49 ± 5.86 mm in men; nose width as 41.65 ± 2.24 in women and as 44.62 ± 4.59 mm in men. In this study, we found lower facial height media value as 5.95 cm in the first group, as 6.20 cm in the second group, as 6.17 cm in the third group and as 6.20 cm in the fourth group; total nasal length median value as 5.25 cm in the first group, as 5.69 cm in the second group, as 5.88 cm in the third group and as 5.25 cm in the fourth group; nose width median value as 3.41 cm in the first group, as 3.47 cm in the second group, as 3.65 cm in third group and as 3.37 cm in the fourth group.…”
Section: Discussionmentioning
confidence: 99%
“…Çalışmamıza benzer bir çalışma Kosif ve arkadaşları tarafından yapılmış olup, yüzde yapılan ölçümler içinden dudak kalınlıkları, dudak tipleri ve philtrum uzunluğu kişilik testi ile anlamlı korelasyonlar vermiştir. Göz, burun ve yüz yükseklikleri araştırılmamıştır (20). Biz çalışmamızda katılımcıların yüzündeki morfometrik ölçümlerle, kişilik testi sonuçları arasındaki anlamlı ilişkiyi araştırdık.…”
Section: Discussionunclassified
“…Tere are diferent types of human lips, so it is necessary to have a reference for the types of lip shapes common to humans. Reference to the shape of the lip from [15] has been adapted as shown in Figure 2. From the types of lip shapes, it is hoped that it can represent the overall shape of the human lips.…”
Section: Data Acquisitionmentioning
confidence: 99%
“…Tis study addresses these challenges by proposing an Indonesian lip-reading dataset, as well as a detection and recognition system based on the diversity of lip shapes considering the unique characteristics of eight types of lip shapes [15]. Te MediaPipe face mesh [16] was used for the detection and elimination of surrounding noise, and the long-term recurrent convolutional network (LRCN) [17] for the classifcation of utterances.…”
Section: Introductionmentioning
confidence: 99%